TEACHERS' CORRECTIVE FEEDBACK ON STUDENTS' SPOKEN ERRORS IN SECOND GRADE EFL CLASSROOOMS OF A SENIOR HIGH SCHOOL - Khaerunisa, - (2006)
This study was trying to examine the patterns of teacher's corrective feedback in Senior high school. The study focused on the roles the teachers playedin response to the students' spoken errors, the spoken errors the teachers chose to correct, the teachers' rationale for correcting them, and the corrective feedback strategies the teachers employed to correct the errors. To elicit the data concerning teachers' corrective feedback, this study employed semi-qualitative approach. The qualitative method was largely employed to understand the phenomena, and some quantification of data is also used to describe the numbers and percentages of the corrected errors and of the applied corrective feedback. There were two kinds of instruments; classroom observation and interview in four second grade EFL classrooms.The study revealed some results. First, there are two kinds of roles the respondents played in response to the students' spoken errors: Mr Busybody who corrects every error the students produced, and Mr Aloof who corrected no students' spoken errors.Second, the spoken errors the teacher chose to correct were translation errors, phonological errors, and syntactic errors. These corrected errors mostly occurred during teacher-learner interaction and the deviant forms of the language items which are within the teacher's linguistic knowledge. These errors would be very likely not to escape the teacher's attention. Third, the teacher's reasons of correcting the errors were due to fossilization, learning, and professional factors. Fourth, the teacher appeared to be able to employ various types of corrective feedback strategies: elicitation, metalinguistic clues, explicit correction, recast and repetition. In contrast to the finding of the previous studies (Lyster and Ranta (1997); Pannova and Lyster (1998)), this study found that elicitation and metalinguistic clues were the most frequently used types of corrective feedback.These findings suggest that the teachers seemed to perceive students' errors merely as the deviant utterances from the target language norms which need to be corrected. The error is not yet seen as an indication of learning process taking place in the learners' minds, and a clue of learning progress the learners may achieve.This study, hopefully, would be able to give some pictures of how students' errors were treated in the language classrooms, and a glimpse insight of the teachers' abilities in identifying errors.